2022
DOI: 10.3389/fphar.2022.852604
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Efficacy Protocol of Yinhuapinggan Granules: A Randomized, Double-Blind, Parallel, and Controlled Clinical Trial Program for the Intervention of Community-Acquired Drug-Resistant Bacterial Pneumonia as a Complementary Therapy

Abstract: Background: Community-acquired bacterial pneumonia (CABP) is an important health care concern in the worldwide, and is associated with significant morbidity, mortality, and health care expenditure. Streptococcus pneumoniae is the most frequent causative pathogen of CABP. Common treatment for hospitalized patients with CABP is empiric antibiotic therapy using β-lactams in combination with macrolides, respiratory fluoroquinolones, or tetracyclines. However, overuse of antibiotics has led to an increased incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…At the same time, recent research showed that YPG and its components have significant inhibitory effects on the proliferation of the H1N1 virus [3]. Meanwhile, a randomized, double-blind, parallel, controlled clinical trial program with a total of 240 participants is in progress to test the clinical Molecules 2024, 29, 2300 2 of 23 efficacy of YPG as a complementary therapy against community-acquired drug-resistant bacterial pneumonia [4].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, recent research showed that YPG and its components have significant inhibitory effects on the proliferation of the H1N1 virus [3]. Meanwhile, a randomized, double-blind, parallel, controlled clinical trial program with a total of 240 participants is in progress to test the clinical Molecules 2024, 29, 2300 2 of 23 efficacy of YPG as a complementary therapy against community-acquired drug-resistant bacterial pneumonia [4].…”
Section: Introductionmentioning
confidence: 99%
“…PD is also an important component of traditional Chinese medicine compounds, Yinhuapinggan (YHPG) granules used to treat respiratory infections 12 16 . YHPG was composed of six herbs, which had the effect of clearing heat and detoxifying 17 . Investigations into the pharmacodynamics and mechanism of YHPG in animals and cells had demonstrated its antiviral, antibacterial, antipyretic, analgesic, cough relieving, and immunomodulatory effects 17 .…”
Section: Introductionmentioning
confidence: 99%
“…YHPG was composed of six herbs, which had the effect of clearing heat and detoxifying 17 . Investigations into the pharmacodynamics and mechanism of YHPG in animals and cells had demonstrated its antiviral, antibacterial, antipyretic, analgesic, cough relieving, and immunomodulatory effects 17 . In previous studies, we found that YHPG had a positive effect on the treatment of viral infectious respiratory diseases 14 .…”
Section: Introductionmentioning
confidence: 99%